Comparison of Estradiol levels in Polycystic Ovary Syndrome and non-Polycystic Ovary Syndrome Infertile Patients - Khattak, Madiha; Sultana, Nuzhat; Fasih Khattak, Almas; Usman, Robina; Khattak, Arshia (ADVANCES IN BASIC MEDICAL SCIENCES, 2022)
ABSTRACT: Background: Polycystic ovary syndrome (PCOS) is the most common endocrine hormonal derangement in females leading to infertility. It is characterized by altered hormonal profile along with metabolic and fertility problems. Objective: To find out the estradiol levels in PCOS and non PCOS infertile patients. Methodology: This was a comparative cross-sectional study. It was carried out at Jinnahabad Medical Center which is a private hospital in Abbottabad from January 2013 to July 2013. We took 40 PCOS patients and 40 non-PCOS infertile patients depending on history, clinical examination and ultrasound scans after taking informed consent. Early follicular phase blood samples were taken. Results: The data was analyzed by SPSS software version 19. Student t-test was applied. P-value was greater than 0.05 and was non- significant. Conclusion: The Estradiol levels of PCOS and non-PCOS infertile patients were not significantly different from each other. Keywords: Polycystic ovary syndrome, Estradiol, Infertility.